A Causality Relationship Between Tax Revenue and Government Expenditure In Indonesia - Jaka Sriyana (Economic Journal of Emerging Markets, 2009)
This paper attempts to model the relationship between tax revenue and government expenditurefor Indonesia over the period 1970-2007. The empirical analysis employs tests of cointegrationand Vector Error Correction Model (VECM). The empirical evidence suggests thatthere is a long run relationship between tax and government expenditure, but in the shortterm, the model explains unidirectional causality relationship, namely from tax revenue togovern ment expenditure This finding indicates that the budget deficit increase continuously,which threaten the fiscal sustainability in the long term. It suggests that the governmentshould organize a better management on public finance policies to support the tax-spend fiscalpolicy.Key words: tax, government, causality, expenditure, cointegration.